Quantitative security analysis of three-level unitary operations in quantum secret sharing without entanglement - Xu, Juan; Li, Xi; Han, Yunguang; Zhou, Yuqian; Liu, Zhihao; Zhang, Zhengye; Song, Yinxiu (Frontiers in Physics, 2023)
Quantum secret sharing (QSS) protocols without entanglement have showed high security by virtue of the characteristics of quantum mechanics. However, it is still a challenge to compare the security of such protocols depending on quantitative security analysis. Based on our previous security analysis work on those using single qubits and two-level unitary operations, QSS protocols with single qutrits and three-level unitary operations are concerned in this paper. Under Bell state attack we propose, the quantitative security analyses according to different three-level unitary operations are provided respectively in the one-step and two-step situations. Finally, important conclusions are drawn for designing and implementing such QSS protocols. The method and results may also contribute to analyze the security of other high-level quantum cryptography schemes based on unitary operations.